Keterlibatan Multistakeholders dalam Mengembangkan Produktivitas dan Daya Saing Industri Kreatif Berbasis Pariwisata - Risty, Fiksy Indah Nurani (Rumah Jurnal UNEJ, 2024)
Creative economy and tourism industry are two things that influence each other and can synergize if managed properly. Tourism-based creative industry is one of the creative economy sectors that has great potential for development in Indonesia. Opportunities for the creative industry across Indonesia have become widely open as an impact of diversity in arts, culture and cultural heritage. However, its development requires the roles and involvement of various stakeholders or multi-stakeholders. Stakeholders are individuals or groups involved in tourism development. In tourism destination management efforts, stakeholders are one of the important factors in maintaining competitiveness. This is the main factor in facing the dynamics and development of tourism markets. The aim of this study is to analyse the involvement of roles among stakeholders in improving productivity and competitiveness of tourism-based creative industries. The research method uses a qualitative approach. Multi-stakeholder involvement plays a significant role in developing productivity and competitiveness of tourism-based creative industries. Various stakeholders such as government, non-government organizations, industry players, and local communities contribute to various aspects of creative industry development. Based on these results, the implications are the need to strengthen cooperation between stakeholders, empower local communities, promote innovation and collaboration, and develop stakeholder capacities to improve productivity and competitiveness of tourism-based creative industries.